Spatiotemporally Coupled Photoactivity of Phthalocyanine–Peptide Conjugate Self‐Assemblies for Adaptive Tumor Theranostics - Li, Shukun; Zhao, Luyang; Chang, Rui; Xing, Ruirui; Yan, Xuehai (Chemistry : a European journal, 2019)
Spatiotemporally coupled tumor phototheranostic platforms offer a flexible and precise system that takes the biological interaction between tumors and photoactive agents into consideration for optimizing treatment, which is highly consistent with precision medicine. However, the fabrication of monocomponent‐based photoactive agents applicable to multifold imaging techniques and multiple therapies in a facile way remains challenging. In this study, we developed simple phthalocyanine–peptide (PF) conjugate‐based monocomponent nanoparticles with spatiotemporally coupled photoactivity for adaptive tumor theranostics. The self‐assembled PF nanoparticles possess well‐defined spherical nanostructures and excellent colloidal stability along with supramolecular photothermal effects. Importantly, the PF nanoparticles showed switchable photoactivity triggered by their interactions with the cell membrane, which enables an adaptive transformation from photothermal therapy (PTT) and photoacoustic imaging (PAI) to photodynamic therapy (PDT) and corresponding fluorescence imaging (FI). Theranostic modalities are integrated in a spatiotemporally coupled manner, providing a facile, biocompatible and effective route for localized tumor phototherapy. This study offers a flexible and versatile strategy to integrate multiple theranostic modalities into a single component so that it can realize its full potential and thereby amplify its therapeutic efficacy, creating promising opportunities for the design of theranostics and further highlighting their clinical prospects to the diagnosis and treatment of cancers. Self‐assembled phthalocyanine–peptide conjugate‐based monocomponent nanoparticles possess spatiotemporally switchable photoactivities, enables multimodal theranostics including photothermal therapy, photoacoustic imaging, photodynamic therapy and fluorescence imaging in a pure conjugate, which provides a facile, biocompatible and effective route for localized adaptive tumor theranostics.